Técnica de anatomización de postes de fibra de vidrio en dientes endodonciados. Una revisión de la literatura - Reyes Jiménez, Marvin Armando (2024)
This literature review explores the technique of anatomizing fiberglass posts in endodontically treated teeth, with the aim of assessing its effectiveness and comparing the fracture resistance of teeth restored with modified and unmodified fiberglass posts. The results show that anatomization is highly effective for dental rehabilitation, providing precise adaptation to the root canal and facilitating strong adhesion through the use of specific adhesive cements. This method not only improves the retention and stability of the restoration but also increases its durability and long-term functionality. The review shows that customizing prefabricated fiberglass posts increases fracture resistance and improves failure patterns, which maintains dental integrity. In addition, this technique provides important aesthetic benefits, particularly for anterior teeth, and is particularly beneficial for teeth with larger canals. Furthermore, the precise cementation methods and accurate post adaptation contribute to the stability and long-term success of dental restorations